The antimetastatic and antiangiogenesis effects of kefir water on murine breast cancer cells - Zamberi, Nur Rizi; Abu, Nadiah; Mohamed, Nurul Elyani; Nordin, Noraini; Yeap, Swee Keong; Boon, Kee Beh; Zakaria, Zuki Abu Bakar; Nik Abdul Rahman, Nik Mohd Afizan; Alitheen, Noorjahan Banu (Sage Publications, 2016)
Background. Kefir is a unique cultured product that contains beneficial probiotics. Kefir culture from other parts of the world exhibits numerous beneficial qualities such as anti-inflammatory, immunomodulation, and anticancer effects. Nevertheless, kefir cultures from different parts of the world exert different effects because of variation in culture conditions and media. Breast cancer is the leading cancer in women, and metastasis is the major cause of death associated with breast cancer. The antimetastatic and antiangiogenic effects of kefir water made from kefir grains cultured in Malaysia were studied in 4T1 breast cancer cells. Methods. 4T1 cancer cells were treated with kefir water in vitro to assess its antimigration and anti-invasion effects. BALB/c mice were injected with 4T1 cancer cells and treated orally with kefir water for 28 days. Results. Kefir water was cytotoxic toward 4T1 cells at IC50 (half-maximal inhibitory concentration) of 12.5 and 8.33 mg/mL for 48 and 72 hours, respectively. A significant reduction in tumor size and weight (0.9132 ± 0.219 g) and a substantial increase in helper T cells (5-fold) and cytotoxic T cells (7-fold) were observed in the kefir water–treated group. Proinflammatory and proangiogenic markers were significantly reduced in the kefir water–treated group. Conclusions. Kefir water inhibited tumor proliferation in vitro and in vivo mainly through cancer cell apoptosis, immunomodulation by stimulating T helper cells and cytotoxic T cells, and anti-inflammatory, antimetastatic, and antiangiogenesis effects. This study brought out the potential of the probiotic beverage kefir water in cancer treatment.